2018
DOI: 10.1002/jccs.201800310
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine‐functionalized magnetic microspheres and stable isotope labeled internal standards for reducing matrix effect in determination of five opium alkaloids by liquid chromatography‐quadrupole linear ion trap mass spectrometry

Abstract: Amantadine-functionalized magnetic microspheres (Fe 3 O 4 @SiO 2 @ADME) were prepared and applied as magnetic solid-phase extraction (MSPE) adsorbents for the enrichment and analysis of five opium alkaloids in hotpot seasoning samples with liquid chromatography coupled to quadrupole linear ion trap mass spectrometry (LC-QqQ LIT -MS/MS). The adsorbents could strongly adsorb the opium alkaloids via hydrogen-bonding, hydrophobic, and π-π conjugation effects. The established MSPE, combined with stable isotope-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…To perform this, the amount of CTAB present in the materials was monitored after the removal treatment by using FT-IR spectroscopy before the functionalisation process by checking the presence of the bands of the -CH 2 and -CH 3 groups from CTAB at 2855 cm −1 and 2925 cm −1 , respectively. The first treatment was performed with a Soxhlet acetone extraction, as in most studies [ 22 , 23 , 36 , 37 ]. However, the intensity of these bands was remarkable ( Figure S3a , spectrum 2), which showed that this treatment was not effective in eliminating the surfactant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To perform this, the amount of CTAB present in the materials was monitored after the removal treatment by using FT-IR spectroscopy before the functionalisation process by checking the presence of the bands of the -CH 2 and -CH 3 groups from CTAB at 2855 cm −1 and 2925 cm −1 , respectively. The first treatment was performed with a Soxhlet acetone extraction, as in most studies [ 22 , 23 , 36 , 37 ]. However, the intensity of these bands was remarkable ( Figure S3a , spectrum 2), which showed that this treatment was not effective in eliminating the surfactant.…”
Section: Resultsmentioning
confidence: 99%
“…As has been observed, the most used separation technique is HPLC, although there are authors who also use UHPLC because it has the advantage of reducing analysis times. Chromatography times for methods developed with HPLC-MS/MS are between 15 and 30 min [ 6 , 20 ], while methods developed with UHPLC-MS/MS take between 7 and 10 min [ 1 , 22 ]. A noteworthy aspect of this proposed method is that only 5 min were sufficient to efficiently quantify the six opium alkaloids, which is considerably less time than the methods already developed to quantify opioids in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is equipped with a triple quadrupole (TQ) detector with electrospray ionization in the positive mode (ESI+) and multiple reaction monitoring (MRM) for multiple analyte detection. ,,, Regarding sample treatment, until now, solid–liquid extraction (SLE) of OAs from poppy seeds has been performed in most studies. ,,, However, it is essential to carry out an adequate sample treatment that includes a preconcentration and/or purification step to eliminate the possible matrix effects, thus avoiding erroneous results and extending the useful life of the chromatographic column and MS detector. For this reason, a solid-phase extraction (SPE) step is used in some studies. ,, In addition, the magnetic dispersive SPE (MSPE) version has also been evaluated for this task , as the sorbent material can be quickly separated from the solution by using an external magnetic field, instead of filtration or high-speed centrifugation as required in common dispersive SPE. Then, MSPE is a simpler, faster, easily miniaturized, and environmentally friendly preconcentration/purification technique .…”
Section: Introductionmentioning
confidence: 99%